Kreativitas Siswa Pada Pembelajaran Bordir Kelas XI Jurusan Desain Produksi Kriya Tekstil Di SMK Negeri 4 Pariaman - Husni, Rafikah; Yasnidawati, Yasnidawati; Novrita, Sri Zulfia (Journal of Home Economics and Tourism, 2015)
The background of this research was the lack of students’ creativity level in learning the embroidery in SMK 4 Pariaman. The lack of students’ creativity of their self-confidence and aotonomy in desingning motives, their creativity in combining the color of materials and yarns and their creativity in sewing the embroidery are the indicators of the lack od students’ creativity development. The objective of this research was to describe the students creativity in learning embroydery. This research was a descriptive research which was conducted by quantitative approach, the consisted of (1) self confidence and anatomy, (2) curiosity, and (3) diligent. The data was primary data. The population in this research was the grade XI students in learning the embroidery at textile craft production design department at SMKN 4 Pariaman. They were consisted of 22 students. The data was collected by using the scale likert and questionnaire. Then, the data was analysed by using descriptive analysis in counting the persentage which consisted of maximum and minimum valves, mean, mode, as well as the standard deviation of each indicator and variable. The resultof this reserach shows that the students creativity in learning the embroidery in grade XI of textile craft production design department in SMKN 4 Pariaman is in the medium category (58,15%), its indicators: (1) self_confidence and autonomy is in the medium category (53,33%), (2) the curiosity is in the medium category (60,29%), (3) diligent is in the medium category (60,71%). Keyword: creativity of students, learning embroidery